Effect of Varying Light Intensity on Growth Performance and Carcass Characteristics of Broiler Chickens Grown to Heavy Weights - Olanrewaju , H.A.; Purswell, J.L.; Collier, S.D.; Branton, S.L. (International Journal of Poultry Science, 2011)
This study investigated the effects of varying levels of light intensities (25, 10, 5, 2.5 and 0.2 lx) on growth performance and carcass characteristics of broiler chickens grown to heavy weights. Four identical trials were conducted with two replications per trial. In each trial, 600 1-d-old Ross 308 chicks were randomly distributed into 10 environmentally controlled chambers (30 male and 30 female chicks/chamber). Each chamber was randomly assigned one of five light intensities from d 22 to 56. Feed and water were provided ad libitum. Birds were provided a four phase-feeding program (starter, grower, finisher and withdrawal). Birds and feed were weighed on 0, 14, 21, 28, 42 and 56 d of age for growth performance. Also at 56 d of age, 20 birds (10 males and 10 females) from each chamber were randomly selected and processed to determine weights and yields. There was no effect of light intensity on growth performance, except significant (p<0.054) difference in FCR on 28 d of age under 25 and 5 lx. Broilers reared under 5 lx had significantly higher live weight (p<0.046) and carcass weight (p<0.026) in comparison with 0.2 and 25 lx. Birds reared under 5 and 10 lx had significantly higher fillet (p<0.025) and tender (p<0.034) weights when compared with birds reared under 0.2 and 25 lx. Mortality was not affected by light intensity treatments. In addition, plasma corticosterone concentrations were not statistically affected by light intensity, suggesting an absence of physiological stress. These results indicate that the range of light intensity used in this study has no effect on most production performances of broilers reared up to 56 d of age, but did affect some carcass characteristics. Therefore, using lower lighting intensity may be beneficial to commercial poultry facilities that are using low lighting environment to reduce hyperactivity, pecking damage and energy costs without physiological stress effects on broiler welfare.